Indikationen zur chirurgischen und interventionellen Behandlung der akuten Pankreatitis - Radulova-Mauersberger, Olga; Belyaev, Orlin; Birgin, Emrullah; Bösch, Florian; Brunner, Maximilian; Müller-Debus, Charlotte Friederieke; Wellner, Ulrich Friedrich; Grützmann, Robert; Keck, Tobias; Werner, Jens; Uhl, Waldemar; Witzigmann, Helmut (Zentralblatt für Chirurgie, 2020)
BACKGROUND: 15 to 20% of patients with acute pancreatitis develop necrosis of the pancreatic parenchyma or extrapancreatic tissue. The disease is associated with a mortality rate of up to 20%. The mainstays of treatment consist of intensive medical care and surgical and interventional therapy. METHODS: A systematic literature search focused on indications for surgical and interventional therapy of necrotising pancreatitis. 85 articles were analysed for this review. By using the Delphi method, the results were presented to the quality committee for pancreas diseases of the German Society for General and Visceral Surgery and to expert pancreatologists in an interactive conference using plenary voting during the visceral medicine congress 2019 in Wiesbaden. For the finalised recommendations, an agreement of 84% of participants was achieved. RESULTS: Documented or clinical suspicion of infected, necrotising pancreatitis are indications for surgical and interventional therapy (recommendation grade: strong; evidence grade; low). Sterile necrosis is a less common indication for intervention due to late complications or persistent severe pancreatitis. Invasive interventions should be delayed when possible until four weeks after onset of pancreatitis. Optimal treatment strategy consists of a "step-up approach" (evidence grade: high; recommendation grade: strong). The first step is catheter drainage, followed, if necessary, by minimally invasive surgical or interventional necrosectomy. If minimally invasive techniques do not result in clinical improvement, open necrosectomy is necessary. 35 to 50% of patients are successfully treated with drainage alone. Indications for emergency intervention are bowel perforation, bowel ischemia and bleeding. Surgical decompression of abdominal compartment syndrome is indicated if the patient is refractory to medical treatment and percutaneous drainage. Abscesses and symptomatic pseudocysts are indications for interventional drainage. Early cholecystectomy during index admission is recommended for patients with mild biliary pancreatitis. Cholecystectomy should be delayed after severe, biliary pancreatitis. CONCLUSION: The recommendations for surgical an interventional therapy of necrotising pancreatitis address the basis of current indications in literature. They should serve in daily practice as a reference standard for decision making in multidisciplinary teams.
CRIS-Team Scopus Importer:2020-06-30